Day 2 Tue, February 05, 2013 2013
DOI: 10.2118/163839-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Measurement of Hydraulic Fracture Conductivities in the Barnett Shale

Abstract: Horizontal wells intersecting multistage transverse fractures created by low viscosity fracturing fluid with low proppant loadings are the key to revitalizing production from the Mississippian Barnett shale of the Fort Worth Basin in Texas. However, direct laboratory measurements of both natural and induced fracture conductivities under realistic experimental design conditions are needed for reliable well performance analysis and fracture design optimization.In this work, a series of experiments were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…According to experimental results [21], the relationship between the effective permeability and gas pressure can be written as:…”
Section: Stress Dependence and High-velocity Non-darcy Flow In Hydraumentioning
confidence: 99%
“…According to experimental results [21], the relationship between the effective permeability and gas pressure can be written as:…”
Section: Stress Dependence and High-velocity Non-darcy Flow In Hydraumentioning
confidence: 99%
“…As Kamenov et al (2014) has pointed out that due to the surface asperity, proppants tend to collect at the valleys of the fracture surface. At the same concentration, the initial propped width of the rough fracture is larger than the fracture width where proppants are evenly distributed due to the thicker sand collections at the surface valleys (Fig.…”
Section: Calculation Of Fracture Conductivitymentioning
confidence: 99%
“…Kamenov et al (2013) performed successful laboratory fracture conductivity measurements using Barnett Shale outcrop samples. They concluded that unpropped induced fractures after removal of free particles and debris are conductive, and that propped fracture conductivity increases with larger proppant size and higher proppant concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, proppant dominated fracture conductivity declines more slowly than surface-dominated fracture conductivity. Kamenov et al (2013) provided an experiment procedure with careful control on error, which can be reproduced to measure fracture conductivity of real shale rough fracture samples. However, the effects of rock mechanics and mineralogical composition of the shale samples used in conductivity experiments have not been discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation